Regional regularities of variations of facial composition and collector properties of Early Pliocene rocks (within the limits of the Lower Kura depression) - A. A. Feyzullayev; V. N. Lunina; G. G. Ismaylova; I. M. Mamedova; N. M. Sadykhov; G. T. Akhmedova; E. H. Guliev (Геофизический журнал, 2019)
Complex analysis (litho-facial, mineralogical, chemical composition and reservoir properties of rocks) of Early Pliocene of Productive series has been conducted and regional regularities of their variations within the limits of Kurovdag-Neftechala anticline zone of Lower Kura depression have been considered. It has been found that in lithological composition of the rocks studied siltstone fraction predominates and the main rock forming minerals are quartz and feldspars; calcite content is insignificant. According to the results of microphotographs analysis (thin sections) spatial variability of geometry of pore has been found as well as of forms and sizes of grains, their average diameter decreasing from NW (Kurovdag area) to SE (Neftechala area). Decrease of ra-tios of sandy fraction and clayish one, decrease of the sandy interbeds number, increase of carbonate content in siltstones have been recorded in the same direction. There is no clearly expressed regularity in porosity and permeability in this direction except Babazanan area where permeability of core samples is low. Regional character of changes of rock litho-facial properties correlates well with oil and gas content in Productive series as well as with properties of oil and gas. Decrease of hydrocarbon reserves, initial yields of wells, content of methane homologues in extracted gas, change of gas-oil ratio and oil density from NW to SE has been revealed, related most probably with growth of clayiness of reservoir rock. Results of conducted studies may be used while planning further petroleum engineering works on the studied fields.